Answer:
solution :
x = 4
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
5*(x-10)-(30-15*x)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
5 • (x - 10) - (30 - 15x) = 0
Step 2 :
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
20x - 80 = 20 • (x - 4)
Equation at the end of step 3 :
20 • (x - 4) = 0
Step 4 :
Equations which are never true :
4.1 Solve : 20 = 0
Step-by-step explanation:
Yes, 6 over 2 equals to 3.
6 = 2 x 3
6/2 = (2 x 3)/2 = 3
Answer:
-2 and 26
Step-by-step explanation:
-2*26=-52
-2+26=24
Answer:
25pi. 36pi
10pi. 12pi
--------------------------
9pi. 49pi
6pi. 14pi
Answer:
0.375
Step-by-step explanation: